Numerical and biomass growth study of Bulimulus bonariensis (Rafinesque, 1833) (Gastropoda: Bulimulidae) under laboratory conditions - Díaz, Ana Carolina (2024)
Bulimulus bonariensis is considered a species of relevance to agribusiness, having been declared a pest with indirect damage because of its negative effects on several crops such as soybeans, chickpeas, and corn in central and northern Argentina. The objective of this work was to analyze the growth pattern of a population born under laboratory conditions, to explore population aspects such as survival and mortality, to estimate the age and size at gonadal maturity and first reproduction, and to contribute to the knowledge of the reproductive biology of this gastropod. From the clutches obtained, the basic biologic parameters were calculated and the individuals hatched under laboratory conditions counted and measured every two weeks. The clutches contained an average of 44 eggs, which took about 13.7 days to hatch at a birth rate of 41.82%. The growth pattern in the five clutches was analyzed individually, and the logistic model used was the one with the highest degree of fit to that observed growth pattern, followed by the Gompertz model, and finally the von Bertalanffy model. In addition, the models were applied to the 102 specimens analyzed together as a cohort, where the best fitting model was also proved to be the logistic growth model. A concave type III survival curve was obtained from the horizontal life table. The cohort was reduced by 48% during the first 50 days after birth. Beyond one month of hatching, life expectancy gradually increased and remained high between 65 302 days of life. After day 330, life expectancy decreased and only 13.72% exceeded one year of birth, with an average length of 16.68 mm. The last specimen died after 23 months at a total length of 20.24 mm, and the life expectancy was estimated at almost three years. In addition, it was inferred that gonadal maturity, when these gastropods reach 12 mm of total shell length, is reached after 200 days of life. Therefore, the individuals that are born are able to reproduce for the first time a year after birth, when they have the approximate size of 16.68 mm.